1997
DOI: 10.1136/hrt.78.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the value of necropsy examination in early death after cardiac surgery.

Abstract: Objective-To assess the value of necropsy examination in patients dying soon after cardiac surgery, particularly the proportion of clinical questions answered by the necropsy, the frequency of major unexpected findings, and the limitations of the procedure. Design-A three year prospective study of necropsy examinations in adult patients dying before discharge or within 30 days of cardiac surgery performed under cardiopulmonary bypass in one hospital. Setting-Tertiary referral centre. Results-123 of 2781 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 22 publications
0
29
3
Order By: Relevance
“…The incidence of anoxic brain damage defined as punctate cortical hemorrhage was 7.5% according to Herczeg et al [15], but somewhat lower in this study at 4.9%. On the other hand, our incidence of cerebral hemorrhage was low, only 0.7% compared with the 2.8% found by Lee et al [16] with 108 autopsy patients. Our low incidence of cerebral edema, 51%, compared to the 100% of Herczeg et al [15] is probably due to the definition of cerebral edema, as in the study of Herczeg et al the milder forms of edema were also included.…”
Section: Discussioncontrasting
confidence: 79%
“…The incidence of anoxic brain damage defined as punctate cortical hemorrhage was 7.5% according to Herczeg et al [15], but somewhat lower in this study at 4.9%. On the other hand, our incidence of cerebral hemorrhage was low, only 0.7% compared with the 2.8% found by Lee et al [16] with 108 autopsy patients. Our low incidence of cerebral edema, 51%, compared to the 100% of Herczeg et al [15] is probably due to the definition of cerebral edema, as in the study of Herczeg et al the milder forms of edema were also included.…”
Section: Discussioncontrasting
confidence: 79%
“…Despite extensive investigations in this field since the introduction of CABG in the late 1960s, only relatively few clinicopathological studies on causes of death and complications have yet been reported [6,16,18,29]. This may partly be explained by the fact that in the last decades the autopsy rate has shown continual declination in the western world.…”
Section: Discussionmentioning
confidence: 82%
“…1 After cardiac surgery, VTE has been reported as a common cause of postoperative death, [2][3][4] and it is the fifth most common reason for hospital readmission after coronary artery bypass graft surgery (CABG). 5 Recent reports in the cardiac surgery literature have documented rates of clinically apparent VTE ranging from 0.5% to 1.3%, [5][6][7][8] although higher rates have been seen in studies using routine postoperative ultrasound surveillance.…”
mentioning
confidence: 99%